Bacterial Vaginosis Awareness Among Pediatric and Adolescent Age Groups in Saudi Arabia - Ettedal A. Aljahdali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Bacterial vaginosis has turned into one of the most common medical condition among women here in Saudi Arabia. Several contributing factors, including the lack of knowledge have been affi liated with this infection and yet the cause remains uncertain. The aim of this study is to determine the level of population awareness regarding bacterial vaginosis both in pediatric and adolescent age groups. It also seeks to evaluate the relationship between the outlined causative factors and bacterial vaginosis. A cross sectional descriptive study was conducted using a self-developed questionnaire and was distributed among the participants (adolescent girls, mothers and non-mothers) over a period of four months from December 2013 until March 2014 at King Abdulaziz Hospital, Jeddah, Saudi Arabia. The study revealed that a remarkable number of the mother respondents demonstrated awareness on bacterial vaginosis in pre-pubertal and adolescent age group (289, 96.98%). The sample of population under the pre-pubertal age group (122, 40.94%) had higher incidence rates of bacterial vaginosis in comparison with the adolescents and non-mothers (17, 6.25%). Advanced research is required to better understand the pathological and physiological mechanisms of bacterial vaginosis. Continuing studies are necessary to enhance the accuracy of its diagnosis and modalities of treatment.